(3x+1)(2x-8)-6x(x+4)=

Simple and best practice solution for (3x+1)(2x-8)-6x(x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x+1)(2x-8)-6x(x+4)= equation:


Simplifying
(3x + 1)(2x + -8) + -6x(x + 4) = 0

Reorder the terms:
(1 + 3x)(2x + -8) + -6x(x + 4) = 0

Reorder the terms:
(1 + 3x)(-8 + 2x) + -6x(x + 4) = 0

Multiply (1 + 3x) * (-8 + 2x)
(1(-8 + 2x) + 3x * (-8 + 2x)) + -6x(x + 4) = 0
((-8 * 1 + 2x * 1) + 3x * (-8 + 2x)) + -6x(x + 4) = 0
((-8 + 2x) + 3x * (-8 + 2x)) + -6x(x + 4) = 0
(-8 + 2x + (-8 * 3x + 2x * 3x)) + -6x(x + 4) = 0
(-8 + 2x + (-24x + 6x2)) + -6x(x + 4) = 0

Combine like terms: 2x + -24x = -22x
(-8 + -22x + 6x2) + -6x(x + 4) = 0

Reorder the terms:
-8 + -22x + 6x2 + -6x(4 + x) = 0
-8 + -22x + 6x2 + (4 * -6x + x * -6x) = 0
-8 + -22x + 6x2 + (-24x + -6x2) = 0

Reorder the terms:
-8 + -22x + -24x + 6x2 + -6x2 = 0

Combine like terms: -22x + -24x = -46x
-8 + -46x + 6x2 + -6x2 = 0

Combine like terms: 6x2 + -6x2 = 0
-8 + -46x + 0 = 0
-8 + -46x = 0

Solving
-8 + -46x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + -46x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + -46x = 0 + 8
-46x = 0 + 8

Combine like terms: 0 + 8 = 8
-46x = 8

Divide each side by '-46'.
x = -0.1739130435

Simplifying
x = -0.1739130435

See similar equations:

| -16x^2+156x+60= | | 16x^2-156x-60= | | 4x-7+2(4x+5)=-2(x+2) | | 5x^2-20x-11= | | 2(v-9)-2=-4(-5v+4)-2v | | 5x^2-20x-3= | | 5x^2+6x-44= | | 2-(y-5)(7-2y)-y(2y-3)= | | -2(8w-1)+4w=6(w+2) | | 4u+3-5(-2u-1)=6(u-1) | | 2x-5*2=10 | | 2y+(5-7y)-9-(3y-2)= | | f(x)=x^3-2.25x^2-3x | | x+2*4=4 | | 427xX=X | | x+0y=4 | | Y+3z=10 | | x-6=-31 | | x(x+3)(x+3)=x(x-3)(x+3) | | 6-4(x+5)=-16 | | K=9r-a | | 2x^2+y^2=17 | | -4(y+5)=8-6(y+7) | | 7y-(8y+9)=10 | | 2x^4+20x^2+18=0 | | 5x=3x-4x+10+2 | | -4(-2)(-5)= | | 4+5=445 | | [(x^3+4X)(6X+2)]+[(3X^2+2X-5)(3X^2+4)]= | | 4+4=445 | | X=(x+500)+4x-1100 | | 2ln(2x)=4-ln(25) |

Equations solver categories